Antimicrobial susceptibility patterns of community-acquired uropathogens in Tehran, Iran - Nasim Kashef; Gholamreza Esmaeeli Djavid; Sahba Shahbazi (Journal of Infection in Developing Countries)
Background: Antibiotic resistance of urinary tract pathogens has increased worldwide. Knowledge of the antibiotic resistance patterns of uropathogens in specific geographical locations is an important factor for choosing an appropriate empirical antimicrobial treatment. The aim of this study was to provide information regarding local resistance patterns of urinary pathogens to the commonly used antibiotics in Tehran, Iran.